2012
DOI: 10.1038/tp.2012.56
|View full text |Cite
|
Sign up to set email alerts
|

Detection of an immature dentate gyrus feature in human schizophrenia/bipolar patients

Abstract: Hippocampus-associated cognitive impairments are a common, highly conserved symptom of both schizophrenia (SCZ) and bipolar disorder (BPD). Although the hippocampus is likely an impacted region in SCZ/BPD patients, the molecular and cellular underpinnings of these impairments are difficult to identify. An emerging class of mouse models for these psychiatric diseases display similar cognitive impairments to those observed in human patients. The hippocampi of these mice possess a conserved pathophysiological alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
122
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(131 citation statements)
references
References 17 publications
(22 reference statements)
6
122
1
Order By: Relevance
“…Commentaries in response to the previous study claim that the implications of the study by Seok et al (1) may well go beyond mice and sepsis (10), and that better definitions of clinical phenotypes, especially in heterogeneous or overlapping conditions such as neurodevelopmental and psychiatric diseases, as well as more emphasis on rigorously defining molecular alterations in human patients, is needed (8). It should be noted that, even for schizophrenia, which could be considered a uniquely human disorder (17), recent mouse models have been developed using an approach similar to those used in the present study that are shown to closely recapitulate not only the clinical or behavioral phenotypes but also the molecular alterations in transcriptional and protein changes in the brain (18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…Commentaries in response to the previous study claim that the implications of the study by Seok et al (1) may well go beyond mice and sepsis (10), and that better definitions of clinical phenotypes, especially in heterogeneous or overlapping conditions such as neurodevelopmental and psychiatric diseases, as well as more emphasis on rigorously defining molecular alterations in human patients, is needed (8). It should be noted that, even for schizophrenia, which could be considered a uniquely human disorder (17), recent mouse models have been developed using an approach similar to those used in the present study that are shown to closely recapitulate not only the clinical or behavioral phenotypes but also the molecular alterations in transcriptional and protein changes in the brain (18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have recently identified the 'immature dentate gyrus' (iDG) as a conserved pathophysiological alteration that is found in neuropsychiatric disorders, including schizophrenia and bipolar disorder (Reif et al, 2006;Yamasaki et al, 2008;Walton et al, 2012;Hagihara et al, 2013;Shin et al, 2013). The observation of iDG was first reported in mice with a heterozygous mutation in the α-calcium/calmodulindependent protein kinase II (Camk2a) gene.…”
Section: Box 1 Immature Dentate Gyrus In Neuropsychiatric Diseasesmentioning
confidence: 99%
“…Finally, hippocampal neurogenesis deficits have been linked to cognitive defects characteristic of depression (Patricio et al, 2013), impairment in early Alzheimer's disease pathology (Demars et al, 2010;Faure et al, 2011;Mu and Gage, 2011;Rodriguez et al, 2011), bipolar disorder (Valvezan and Klein, 2012;Walton et al, 2012) and schizophrenia (SCZD) (Tamminga et al, 2010;Walton et al, 2012;Hagihara et al, 2013). More specifically, alterations in DG granule neuron maturation have been implicated in the etiology and pathogenesis of schizophrenia and bipolar disorder (see Box 1; Reif et al, 2006;Yamasaki et al, 2008;Walton et al, 2012;Hagihara et al, 2013;Shin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…4) This finding showed the face validity of CaMKIIα-hKO mice as a model of schizophrenia because this immaturity in DG was also seen in patients with schizophrenia. 8) Moreover, the formation of IPB mossy fiber could be due to the immaturation of GCs in DG because IPB formation is only seen in immature GCs.…”
Section: Resultsmentioning
confidence: 99%